2016
DOI: 10.1063/1.4940449
|View full text |Cite
|
Sign up to set email alerts
|

A human factors perspective on the use of automated aids in the evaluation of NDT data

Abstract: Abstract. In comparison to manual NDT methods, mechanized NDT is considered to be more reliable for a number of reasons, one of which being that the role of the inspectors and, therewith, the potential for human error, have been reduced. However, human-automation interaction research suggests that in spite of its numerous benefits, automation can lead to new yet unknown risks. One of those risks is inappropriate reliance on automation, which can result in automation misuse and disuse. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Reflecting on Bertovic's (2016) paper in which it was stated that automation poses a potential risk of error within non-destructive testing, the error is largely mitigated with the current operational procedure of two analysis streams and the fact that while the procedure that an analyst follows is now automated, the procedure itself is remains auditable. Furthermore, the industry application of this research is decision support.…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting on Bertovic's (2016) paper in which it was stated that automation poses a potential risk of error within non-destructive testing, the error is largely mitigated with the current operational procedure of two analysis streams and the fact that while the procedure that an analyst follows is now automated, the procedure itself is remains auditable. Furthermore, the industry application of this research is decision support.…”
Section: Resultsmentioning
confidence: 99%
“…It has been posited that an evaluation of the consequences for human operator performance is an important consideration in taking a decision regarding the type and level of automation in any system design (Parasuraman et al, 2000). It has also been argued that because automated systems and aids may fail occasionally, people are necessarily involved as a measure of error recovery and error correction (Bertovic, 2016), thus underscoring not only the human operator as the "common unchanged element in the exponential growth of the automated systems" (Brown, 2016, p. 31) but also the imperativeness of "human-centered automation", an approach which, according to the International Civil Aviation Organization, takes "into account the human element during the design phase so that the resulting system capitalizes upon the relative strengths of humans and computer-based technology" (ICAO, 1994, p. 1).…”
Section: )mentioning
confidence: 99%
“…Quite a staggering number of literature (e.g. Bainbridge, 1983;Bertovic, 2016;Billings, 1996Billings, /1995Brown, 2016;Parasuraman & Riley, 1997;Parasuraman et al, 2000;Sarter et al 1997;Woods, 2001;) has identified and addressed the risks, concerns, and challenges arising from human-automation interactions and the development of automated aids such as a range of technical issues relating to the automation of particular functions and the characteristics of associated sensors, controls, and software (Parasuraman et al, 2000), inappropriate reliance on automation, complacency, and automation bias, which, to say the least, are as relevant to the roles of the air traffic safety electronics personnel (ATSEP) as they are to the activities of air traffic controllers and airlines' flight crew. This is more so given the considerable increases in the complexity and level of automation, which create problems of situational awareness.…”
Section: Automation: Benefits Risks and Concernsmentioning
confidence: 99%
See 2 more Smart Citations